Inventário da Araneofauna de Solo (Arachnida: Araneae) em uma área de Caatinga da Serra de São José, Feira de Santana, Bahia, Brasil - Ferreira, Gutemberg da Silva Cazais (2011)
In the Northeast, few studies have been carried out and, in Bahia, the vast majority of studies carried out are ecological inventories that do not emphasize the identification of spiders. In the present study, an inventory of soil spiders was carried out in an area of the semi-arid region of Bahia, in the Serra de São José, located in the district of Maria Quitéria, about 30 km north of the commercial center of Feira de Santana, Bahia, Brazil. The collections were carried out monthly, during one year, using 40 fall traps per collection. 1,043 spiders were collected, 486 adults and 557 young, distributed in 33 families and 71 species. The most abundant families were: Salticidae, Pholcidae, Zodariidae, Corinnidae, Ctenidae, Palpimanidae and Oonopidae. When the richness was analyzed, Salticidae was the one with the highest species richness, 13, followed by Corinnidae and Oonopidae with seven species, respectively. With regard to diversity, it was Berger-Parker Dominance (Dbp = 0.018) and Equitability J (J = 0.833) were calculated for the species found. The estimated richness for the sampled area was 90 species, based on the Jack 1 estimator, while Bootstrap estimated a richness of 80 species for the region. In assessing the species richness, it was observed that the sampled region, despite suffering from anthropic action, still maintains an expressive number of species for the locality. These results show the importance of expanding knowledge of spider diversity, especially in the semi-arid region, as it demonstrates that it is still lacking studies not only of spiders.